Pertumbuhan Dan Hasil Bawang Merah (Allium Ascalonicum L.) Akibat Pemberian Kompos Limbah Pasar Tradisional Dan Pupuk Npk Pada Tanah Spodosol: Growth And Year Of Shown Onion (Allium Ascalonicum L.) Due To The Application Of Traditional Market Waste Compost And Npk Fertilizer On Spodosol Soil - Daniel Aritonang; Titin Apung Atikah; Siti Zubaidah (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The aims of this study was to determined the effect of aplication waste compost traditional market and NPK to growth and yield of shallots (Allium ascalonicum L.) in the spodosols. This research was yield out in November 2018 until January 2019, at the installation of experimental garden of Agriculture, Faculty of Agriculture, University of Palangkaraya. This study used a Completely Randomized Design (CRD) which consist two factors, processing waste compost traditional market was K0 = 0 tons / ha (Control), K1 = 5 tons / ha, K2 = 10 tons / ha, K3 = 15 tons / ha and NPK treatment was, P0 = 0 kg / ha (Control), P1 = 300 kg / ha, P2 = 400 kg / ha. Each treatment was repeated 3 (three) replications to obtain 36 experimental units. To determined the effect of the treatment given to the yield of the observation, an analysis was carried out. If there was a real influenced from the yield of the analysis, then it will be continued with the BNJ test at the level of ɑ 5%. The yield of the average number of shallot tillers indicate that the combination of distribution waste compost traditional market (K) and NPK (P) with K3P1 treatment (15 tons / ha and 300 kg / ha) was the best combination of variable number of tillers 12,33. The aplication waste compost traditional market at a dose of 10 tons/ha able to increased plant height while 48,16 cm. Dose of 15 tons/ha able to increased number of tillers 9,56, fresh weight 91,80 g and dry tuber weight 53,73 g. While granting NPK at a dose of 400 kg/ha able to increased fresh weight 87,14 g, and dry tuber weight on shallots 49,49 g.